EXECUTIVE NETWORK OF POWER IN THE SYSTEM OF THE DIVISION OF STATE POWER (Conferencea, 2023)
This thesis emphasizes the tasks performed by the Cabinet of Ministers, which implements the executive power in the Constitution of the Republic of Uzbekistan.